Resposta olfativa de fêmeas de Chrysomya Megacephala (F.) (Diptera: Calliphoridae) frente a posturas prévias e caracterização química dos compostos apolares da superfície de seus ovos - Lima, Thiago de [UNESP] (2015)
The choice of oviposition site by adult females of blowflies mainly involves the attraction that the substrate has on these individuals. The sense of smell is used to locate carcass and different semiochemicals are released, attracting different species. The vision plays an important role in landing decision, while contact with the substrate can also provide important information about the place, influencing the posture decision. The blowflies' oviposition process is generally clustered, this is due to release pheromones by females, but there is evidence, in other insects, that eggs could contain some volatile compound that aids in this process. This study aimed to analyze if females of C. megacephala can distinguish, by smell, locations containing eggs from sites containing only substrate, and also, to plot the chemical profile of the chorion of this species' eggs at different stages of development, to verify the presence of possible substances that may affect the female decision when choosing the substrate. The results showed that the females can locate the eggs only by smell and no volatile compounds were found in the eggs' chorion, but a complex mixture of compounds having carbon chain between 11:31 atoms were found. The most representative compounds were linear alkanes, monomethylalkanes, dimethilalkanes and alkenes (hydrocarbons), alcohol, amide and fatty acids. Of these, the compounds cis9-Hexadecenoic acid (palmitoleic acid), n-hexadecanoic acid (palmitic acid) showed differences in concentrations among samples at 0, 3 and 6 hours